Correction: Examining the longitudinal associations between activity limitations, instrumental supports and social participation in osteoarthritis: A CLSA population-based study. - Anthony V Perruccio; Calvin Yip; J Denise Power; Mayilee Canizares; Elizabeth M Badley (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0299894.].